THE SECOND HALF OF THE 19TH AND EARLY 20TH CENTURIES STATE AND MILITARY MANAGEMENT SYSTEM IN THE EMIRATE OF BUKHARA - Abdurazakov Farxad Azatovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article briefly covers the state and military system of government and the socio-political situation in the emirate of Bukhara in the second half of the XIX and early XX centuries.